A new lipase–inorganic hybrid nanoflower with enhanced enzyme activity. Issue 23 (16th February 2016) - Ke, C.; Fan, Y.; Chen, Y.; Xu, L.; Yan, Y.
Abstract : A new hybrid nanoflower biocatalyst was synthesized using the organic component of Burkholderia cepacia lipase and inorganic component of calcium phosphate. Abstract : A new hybrid nanoflower was synthesized using the organic component of Burkholderia cepacia lipase and inorganic component of calcium phosphate. Under the optimum conditions, the nanobiocatalyst exhibited an activity of 849.8 U, 308% folds of the free one, with relatively good stability, highlighting its potential for industrialization.